Exploring surfactant-enhanced stability and thermophysical characteristics of water-ethylene glycol-based Al2O3-TiO2 hybrid nanofluids - Wajiha Tasnim, Urmi; Rahman, Md Mustafizur; K., Kadirgama; D., Ramasamy; Mahendran, Samykano; Ali, M. Y. (WSEAS, 2023)
This study presents an empirical investigation into the impact of surfactant's enhanced stability and thermophysical characteristics of water-ethylene glycol (60:40) based Al2O3-TiO2 hybrid nanofluids. It aims to shed light on the nanofluid's behavior, mainly how surfactants affect its stability and thermal performance, thus contributing to advancements in heat transfer technology and engineering applications. The growing interest in nanofluids, which involves blending nanoparticles with conventional base fluids, spans diverse sectors like solar energy, heat transfer, biomedicine, and aerospace. In this study, Al2O3 and TiO2 nanoparticles are evenly dispersed in a DI-water and ethylene glycol mixture using a 50:50 ratio with a 0.1 % volume concentration. Three surfactants (SDS, SDBS, and PVP) are utilized to investigate the effect of the surfactants on hybrid nanofluids. The study examines the thermophysical characteristics of these hybrid nanofluids across a temperature range of 30 to 70 0C in 20 0C intervals to understand their potential in various industrial applications. The results show the highest stability period for nanofluids with PVP compared to nanofluids with surfactant-free and other surfactants (SDS, SDBS). The thermal conductivity is slightly decreased (max 4.61%) due to PVP surfactant addition compared to other conditions. However, the nanofluids with PVP still exhibit more excellent thermal conductivity value than the base-fluid and significantly reduced viscosity (max 55%). Hence, the enhanced thermal conductivity and reduced viscosity with improved stability due to PVP addition significantly impact heat transfer performance. However, the maximum thermal conductivity was obtained for surfactant-free Al2O3-TiO2/Water-EG-based hybrid nanofluids that reveal a thermal conductivity that is 17.05 % higher than the based fluid. Instead, the lower viscosity of hybrid nanofluids was obtained at 70 0C with the addition of PVP surfactant. Therefore, adding surfactants positively impacts Al2O3-TiO2/Water-EG-based hybrid nanofluids with higher stability, enhancing thermal conductivity and reducing viscosity compared to the based fluids. The results show that adding surfactants at a fixed volume concentration affects thermal conductivity at low temperatures and viscosity at high temperatures, suggesting that these fluids might be used as cooling agents to increase pumping power in industrial applications.